Assessing Impact in Dynamic and Complex Environments: Systemic Action Research and Participatory Systemic Inquiry - Burns, Danny (IDS, 2014)
This CDI Practice Paper is about the uses of Systemic Action Research (SAR) and Participatory Systemic Inquiry (PSI) for impact assessment ( Burns 2006, 2007, 2011, 2012, 2013; Wadsworth 2001, 2010).